Competição de cultivares de soja com capim-arroz (Echinochloa spp.) em terras baixas. - Bastiani, Marlon Ouriques (2015)
Nowadays, with the expansion of soybean cultivation in lowlands in Rio Grande do Sul, barnyardgrass (Echinochloa spp.) has been established as an important weed, causing significant crop yield loss. For this reason, the aim of this research were to: (1) evaluate the effects of temperature and light on germination of barnyardgrass seeds, in different times of storage after dispersal; (2) evaluate the influence of soybean and barnyardgrass coexistence in early stages of development at morphological and physiological characteristics of the species; (3) identify the relative competitiveness of soybean cultivars with barnyardgrass, through replacement series experiments; and (4) investigate different characteristics between soybean cultivars, associated to the crop spatial arrangement, in the competitive ability with barnyardgrass. The experiments were carried in the years of 2013 and 2014, in laboratory and greenhouse of the Departamento de Fitossanidade (FAEM/UFPel), and in the field at the Centro Tecnológico do Chasqueiro (Arroio Grande/RS). The results demonstrate that germination and hypocotyl and radicle growth of barnyardgrass seeds are affected by changes in light and temperature, being the germination reduced when in the absence of light and under low temperature (±15°C). Soybean cultivars, when in initial coexistence with barnyardgrass plants, or barnyardgrass plants in the presence of the soybean cultivars, tend to shade avoidance through the increment of height; however, show reduction in the root system. Soybean cultivars with different morphological and physiological traits show similarity under barnyardgrass competition; for barnyardgrass, the intraspecific competition is more important than interspecific competition with soybean cultivars. The soybean cultivar BMX Potência RR demonstrates superior competitive ability traits with weeds during the early stages of development, when compared to Apollo RR, whereas the practice of the reducing row spacing in soybeans grown in the lowlands, increases the crop yield.